Women’s involvement in coffee agroforestry value-chains: Financial training, Village Savings and Loans Associations, and Decision power in Northwest Vietnam - Simelton, Elisabeth; Mulia, Rachmat; Nguyen, Toan T; Duong, Tuan M; Le, Hieu X; Tran, Ly H; Halbherr, Lucia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Globally, in the coffee sector and smallholder agriculture in developing countries, there is a distinct gender gap in key factors that enable women’s active participation in and contribution to the coffee value chain and in farm and domestic decisions, such as decisions over credit, agricultural inputs, and training opportunities and division of labor and time. This study assesses Village Savings and Loans Associations (VSLA) impacts and related training on gender equality and women’s access to coffee markets in an ongoing coffee- project in northwest Vietnam. All 169 women in this survey received gender equality and finance training, with one group being members of a VSLA and taking out small loans. With Women’s Empowerment in Agriculture Index (WEAI), women rated their perception of their decision-making power over a range of 18 tasks related to household and agricultural responsibilities and use of income and social activities over 18 months. There were significant improvements in decision-making power in categories with previously low participation and increased sharing of domestic responsibilities. The categories with the biggest gains were decision-making over large purchases and use of income, especially for VSLA-members who sought out market information before engaging with potential coffee buyers and enhanced their negotiating abilities to arrange more favorable outcomes successfully. These results indicate that active gender and finance training translated to real changes in gender dynamics, and membership of a VSLA also helped women improve their financial literacy and improve their negotiating abilities. Husbands to women in the study also began to reconsider gender roles and shift towards equal sharing of responsibility and decision- making with their wives. Based on this study, we recommend (1) implementing gender and finance training and enabling access to loans for women as a means for their inclusion in agriculture value chains, and (2) engaging the whole household in gender training in order for all family members to be receptive to adjustments in the gender division of responsibility, labor and decision-making. The results indicate the conditions under which women can benefit from activities involving agroforestry systems that also enhance carbon sequestration for climate change mitigation compared to coffee monoculture.